INQUÉRITO DOMICILIAR SOBRE A COBERTURA VACINAL DO ESQUEMA BÁSICO ATÉ O SEGUNDO ANO DE VIDA, SÃO LUIS, MARANHÃO - Queiroz, Lorena Lauren Chaves (2011)
Vaccination of children in the first year of life is essential for the prevention of various diseases and is one of the factors associated with reduced infant mortality rate. The identification of coverage and the factors responsible for delay or lack of immunization is critical for proper monitoring of vaccination programs and to identify and reach children who are not vaccinated properly. This study aimed to assess vaccination coverage in children 0-18 months of age living in São Luís - MA. The present study describes the results of a household survey to estimate vaccination coverage of the basic scheme until the second year of life in St. Louis - Ma, the cohort born in 2005.The study adopted the methodology recommended by the Pan American Health Organization to conduct surveys of vaccination coverage. Of the 630 planned interviews were conducted 561 (89%). The results show a higher proportion of girls, with a predominance of white children as they raise their levels of education and family income. The distribution of coverage by census tracts is heterogeneous, being the poorest coverage was generally lower socioeconomic strata. The BCG vaccine was the best coverage and there is a significant difference between the production data and data obtained by the inquiry, referring to all vaccines. Vaccination at 18 months (valid doses) are lower than desired, except for BCG (96% coverage). The vaccination coverage (valid doses), complete basic scheme for all the vaccine is only 51%. The survey data were a result far short when compared with administrative data. The data collected show that those recorded by official agencies overestimate the coverage of this population segment suggesting immunity in mass, a factor causing an erroneous false protection and demonstrates a failure in the evaluation of the service, and then other necessary strategies for monitoring actions of the National Immunization Program